Investigation of the thermophysical properties and stability performance of non-covalently functionalized graphene nanoplatelets with Pluronic P-123 in different solvents - Shazali, Siti Shafiah; Amiri, Ahmad; Zubir, Mohd Nashrul Mohd; Rozali, Shaifulazuar; Zabri, Mohd Zakuan; Sabri, Mohd Faizul Mohd; Soleymaniha, Mohammadreza (Elsevier, 2018)
The employment of nanofluids involving the dispersion of nanomaterials in the base fluid has become a major interest of the researchers due to great potential in enhancing the thermophysical properties and heat transfer coefficients. The stability of nanoparticles in base fluids is a major concern with heat transfer applications. The main purpose of this research was to study the stability of graphene nanoplatelets (GNPs) in the presence of Pluronic P-123 surfactant (P-123) in aqueous media and to compare with other common surfactants such as sodium dodecyl sulfate (SDS), cetyltrimethylammonium bromide (CTAB) and Triton X-100 (TX). Each of the surfactants was mixed with GNPs at different ratios of 1:1, 1:2, 1:3 and 1:4. Then, the best ratio with the most stable sample was selected and compared with other samples. The stability of samples was evaluated by using UV-vis spectrometry, zeta potential and particle size distribution. The viscosity and thermal conductivity of the best sample were also measured at different temperatures. High resolution-transmission Electron Microscopy (HR-TEM) was used to characterize the morphology of GNPs. Interestingly, P-123 as a new surfactant showed the best colloidal stability between our samples. Furthermore, the presence of SDS, CTAB and TX surfactants in the nanofluids caused the formation of excessive foam, while P123-GNPs showed no foam-formation after shaking within the given time. It is worthy to highlight that the rises in thermal conductivity and stability in the presence of P-123 were higher than those of other surfactants. Also, the addition of rheological property (viscosity) was found to be insignificant once loading P-123.